2023
DOI: 10.3389/fcell.2023.1226604
|View full text |Cite
|
Sign up to set email alerts
|

Mature iPSC-derived astrocytes of an ALS/FTD patient carrying the TDP43A90V mutation display a mild reactive state and release polyP toxic to motoneurons

Abstract: Astrocytes play a critical role in the maintenance of a healthy central nervous system and astrocyte dysfunction has been implicated in various neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). There is compelling evidence that mouse and human ALS and ALS/FTD astrocytes can reduce the number of healthy wild-type motoneurons (MNs) in co-cultures or after treatment with astrocyte conditioned media (ACM), independently of their genotype. A growing number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 100 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…Non-cell autonomous toxicity to MNs induced by cultured astrocytes harboring diverse ALS-causing gene mutations, including mutations in SOD1, TDP43, and C9ORF72, has also been extensively documented (Dittlau & Bosch, 2023; Garcés et al, 2024; Harten et al, 2021). Our recent study further reveals that excessive inorganic polyphosphate (polyP) released by ALS astrocytes triggers MN death and increases neuronal excitability and Ca 2+ transients (Arredondo et al, 2022; Garcés et al, 2024; Rojas et al, 2023). Additionally, other studies have also shown that astrocyte-mediated MN degeneration is accompanied by several other pathogenic events, including oxidative stress, induction of a cell death signaling (i.e., phosphorylation of c-Abl), and impaired mitochondrial transport (Birger et al, 2019; Dittlau & Bosch, 2023; Fritz et al, 2013; Haidet-Phillips et al, 2011; Harten et al, 2021; Rojas et al, 2014, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Non-cell autonomous toxicity to MNs induced by cultured astrocytes harboring diverse ALS-causing gene mutations, including mutations in SOD1, TDP43, and C9ORF72, has also been extensively documented (Dittlau & Bosch, 2023; Garcés et al, 2024; Harten et al, 2021). Our recent study further reveals that excessive inorganic polyphosphate (polyP) released by ALS astrocytes triggers MN death and increases neuronal excitability and Ca 2+ transients (Arredondo et al, 2022; Garcés et al, 2024; Rojas et al, 2023). Additionally, other studies have also shown that astrocyte-mediated MN degeneration is accompanied by several other pathogenic events, including oxidative stress, induction of a cell death signaling (i.e., phosphorylation of c-Abl), and impaired mitochondrial transport (Birger et al, 2019; Dittlau & Bosch, 2023; Fritz et al, 2013; Haidet-Phillips et al, 2011; Harten et al, 2021; Rojas et al, 2014, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Coexistence or shared clinical, genetic (SOD1, TARDBP, and C9ORF72 et al), and pathological features (TDP-43 inclusions in astrocytes and neurons) have been observed between ALS and FTD [88]. Previous studies have demonstrated that astrocytes from postmortem patients with ALS/FTD also exert detrimental effects on motor neurons [89][90][91]. Astrocyte dysfunction specific to ALS/FTD is comparable to that seen in ALS without FTD; however, there are some distinctions [92].…”
Section: Reactive Astrocytes Are Toxic To Mns In Alsmentioning
confidence: 99%
“…Polyphosphate (polyP), an inorganic neuroactive compound that potentiates the activity of Nav and Kv channels, is synthesized by astrocytes, functioning as a glial messenger to facilitate communications between astrocytes and neurons [110]. Elevated polyP levels were observed in induced pluripotent stem cell (iPSC)-derived astrocytes from mice and postmortem patients with various ALS/FTD-associated mutations (SOD1, TARDBP, and C9ORF72) [89,90]. Similarly, spinal cord sections from patients with familial and sporadic ALS displayed abundant polyP staining signals [89].…”
Section: Polypmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using iPSC-derived astrocytes have provided valuable insights into their role in ALS pathogenesis. Several studies have suggested that iPSC-derived astrocytes from ALS patients are more toxic to motor neurons compared to control astrocytes [195][196][197][198][199][200]. Mechanistically, there have been several proposed mechanisms for how ALS astrocytes mediate their neurotoxicity.…”
Section: Insights From Human Ipsc-derived Microglia and Astrocytes Th...mentioning
confidence: 99%